Effectiveness and safety of generic formulation of meropenem (Penem) for treatment of infections at Siriraj Hospital. - Nasikarn Angkasekwinai (2018)
Generic meropenem (Penem) has been available and was substituted for original meropenem in Siriraj Hospital, but its effectiveness and safety for treatment of infection in clinical setting are the main concern. From July 2007 to July 2010, hospitalized patients aged 18 or older who received meropenem for at least 48 hours were identified retrospectively from the pharmacy database of Siriraj Hospital. 260 patients per group were required to demonstrate non-inferiority of generic meropenem (Penem) versus original meropenem in term of overall favorable outcome. 275 and 273 patients receiving original and generic meropenem were enrolled and analyzed. Overall favorable outcome and overall mortality were comparable between generic and original group (72.5% vs. 65.8%, p = 0.108; 38.6% vs. 39.3%, p = 0.918, respectively). No significant difference of adverse effect was found between two groups. The non-inferiority test indicated that the clinical outcome and overall mortality of the generic meropenem were non-inferior to the original meropenem (p < 0.001, p = 0.005, respectively). The independent factors associated with unfavorable outcome were previous use of an antibiotic, having respiratory tract infection, receiving lower dose and shorter duration of antibiotic. The independent factors associated with the overall mortality were underlying pulmonary disease, previous use of antibiotic, having respiratory tract or catheter related blood stream infection. Treatment with either generic or original meropenem did not relate to unfavorable outcome (p = 0.320) or overall mortality (p = 0.640). Generic meropenem (Penem) was not inferior to original meropenem for therapy of infections in the hospitalized patients at Siriraj Hospital.